Assessment of a composite CC2/DFT procedure for calculating 0–0 excitation energies of organic molecules. (1st December 2016) - Oruganti, Baswanth; Fang, Changfeng; Durbeej, Bo
ABSTRACT: The task to assess the performance of quantum chemical methods in describing electronically excited states has in recent years started to shift from calculation of vertical (Δ E ve ) to calculation of 0–0 excitation energies (Δ E 00 ). Here, based on a set of 66 excited states of organic molecules for which high-resolution experimental Δ E 00 energies are available and for which the approximate coupled-cluster singles and doubles (CC2) method performs particularly well, we explore the possibility to simplify the calculation of CC2-quality Δ E 00 energies using composite procedures that partly replace CC2 with more economical methods. Specifically, we consider procedures that employ CC2 only for the Δ E ve part and density functional theory methods for the cumbersome excited-state geometry optimisations and frequency calculations required to obtain Δ E 00 energies from Δ E ve ones. The results demonstrate that it is indeed possible to both closely (to within 0.06–0.08 eV) and consistently approximate 'true' CC2 Δ E 00 energies in this way, especially when CC2 is combined with hybrid density functionals. Overall, the study highlights the unexploited potential of composite procedures, which hitherto have found widespread use mostly in ground-state chemistry, to also play an important role in facilitating accurate studies of excited states. Abstract :